2015
DOI: 10.1681/asn.2014090881
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Risk for Sudden Cardiac Arrest in ESRD

Abstract: Patients on dialysis are 20 times more likely to have a cardiac arrest compared with the general population. We considered whether inherited factors associate with cardiac arrest among patients on dialysis. From a sample of 647,457 patients on chronic dialysis, we identified 5117 pairs of patients who came from the same family. These patients were each matched to a control subject from the same population. McNemar's tests were used to compare the risk of cardiac arrest between the familial related and unrelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
7
1
Order By: Relevance
“…Multiple prior high-quality publications have resulted from the FMCNA database used in this study. 30,31 Approximately 35% of the United States adult outpatient dialysis population is represented in the FMCNA database. The Clinical Quality Group and Data Entry Error Reduction Task Force at FMCNA mandates protocols and audits incoming information to ensure data are accurately documented for clinical care and Medicare billing.…”
Section: Study Patientsmentioning
confidence: 99%
“…Multiple prior high-quality publications have resulted from the FMCNA database used in this study. 30,31 Approximately 35% of the United States adult outpatient dialysis population is represented in the FMCNA database. The Clinical Quality Group and Data Entry Error Reduction Task Force at FMCNA mandates protocols and audits incoming information to ensure data are accurately documented for clinical care and Medicare billing.…”
Section: Study Patientsmentioning
confidence: 99%
“…A study examining SCD risk among related pairs of dialysis patients found a 70% increased risk of SCD if one relative suffered sudden cardiac death, compared to non-genetically related cohabitating dialysis pairs. 43 Specific genetic loci underlying the increased SCD risk among genetically related hemodialysis patients are unknown, but common variants in loci encoding cardiac ion channels may be involved. 44 Further investigations could identify novel SCD pathways and lead to better identification of those highest at risk for SCD.…”
Section: Pathophysiology Of Scdmentioning
confidence: 99%
“…Additionally (but perhaps not surprisingly), there may be heritability to SCD propensity in dialysis patients. Chan et al recently reported that genetically related family members on dialysis had a 1.7-fold increase in the odds of cardiac arrest compared with matched, unrelated controls (9). In the general population, rare mutations in ionic channels cause several distinct long-QT syndromes, which are associated with a markedly higher risk of SCD (10).…”
Section: Scdmentioning
confidence: 99%